Engagement of the ATR-Dependent DNA Damage Response at the Human Papillomavirus 18 Replication Centers during the Initial Amplification - Reinson, Tormi (American Society for Microbiology, 2013)
We have previously demonstrated that the human papillomavirus (HPV) genome replicates effectively in U2OS cells after transfection using electroporation. The transient extrachromosomal replication, stable maintenance, and late amplification of the viral genome could be studied for high- and low-risk mucosal and cutaneous papillomaviruses. Recent findings indicate that the cellular DNA damage response (DDR) is activated during the HPV life cycle and that the viral replication protein E1 might play a role in this process. We used a U2OS cell-based system to study E1-dependent DDR activation and the involvement of these pathways in viral transient replication. We demonstrated that the E1 protein could cause double-strand DNA breaks in the host genome by directly interacting with DNA. This activity leads to the induction of an ATM-dependent signaling cascade and cell cycle arrest in the S and G(2) phases. However, the transient replication of HPV genomes in U2OS cells induces the ATR-dependent pathway, as shown by the accumulation of γH2AX, ATR-interacting protein (ATRIP), and topoisomerase IIβ-binding protein 1 (TopBP1) in viral replication centers. Viral oncogenes do not play a role in this activation, which is induced only through DNA replication or by replication proteins E1 and E2. The ATR pathway in viral replication centers is likely activated through DNA replication stress and might play an important role in engaging cellular DNA repair/recombination machinery for effective replication of the viral genome upon active amplification.